Enhancing the Reactivity of Phosphate Rocks by Acidulation - . SULAEMAN; . SUPARTO; . EVIATI (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2002)
Indonesian soils requiring a considerably large amount of P fertilizer, since it comprises a large area of phosphate poor soils as Ultisols, Oxisols, and part of Inceptisols. Phosphate rock, particularly of domestic origin, is one of cheapest P sources if it can be applied directly. Acidulation is performed to obtain sufficiently reactive phosphate rocks to give dissolved P (in weak acid) required by annual crops, although not too soluble (in water) to easily leach. The objective of this study was to obtain an efficient P source fertilizer with inexpensive production cost. Eight types of phosphate rocks of domestic and overseas origins were gradually acidulated with sulphuricand phosphoric acids. P fertilizers reactivity were tested by using extracted P content in water, citric acid, and formic acid to total P content ratio. The results showed that the reactivity (in citric acid) orders of tested phosphate rocks were Ciamis > Cileungsi > Algeria > Gresik > Maroko > Sukabumi >Christmas > Senegal. Based on gained regression equation, total P content and reactivity of produced fertilizer for each degree of acidulation with H2SO4 and H3PO4 can be calculated. Water extractant gives the most sensitive indicator value of increased reactivity, followed by citric and formic acids.